The Evolution of Symbolist Ideas in the Zolotoe Runo Magazine - V. D. Ryabchenko (Концепт: философия, религия, культура, 2020)
The article treats the role art magazine Zolotoe runo played in history of symbolist’s theoretical ideas. By 1906, symbolism as a philosophical and aesthetic movement enters a crisis stage (and, then, a renaissance) — the pioneering movement has become utterly formal, tendentious, and has even acquired public recognition, which contradicts the modernist spirit. Zolotoe runo turns into a platform for the adversaries of outdated, decadent or individual symbolism, changing the symbolist nature and landscape. V. F. Khodasevich suggests that not only hasn’t symbolism been yet studied, but it also doesn`t seem to have been even read. This phenomenon and its notion deserve proper research. The scientific community’s interest in this movement is growing, as the importance of symbolism comes to light, and it becomes more evident that it was not only a milestone in history, but it also predetermined many trends in the development of culture and art up to the present day. Apart from that, the extreme heterogeneity within the symbolist movement and its paradoxical and unexpected metamorphoses are rarely understood. Nonetheless, through the analysis of such magazines as Zolotoe runo, and by drawing upon the research of cultural scientists, art historians and literary critics, we can clarify the features of symbolism, contradictory and holistic at the same time.